Maternal fructose consumption impacts on the developmental outcome of its progeny - Cuervo, Sanchez Marié (2021)
Recent epidemiological evidence suggests that exposure to mater- nal obesity increases the risk of neurodevelopmental disorders in offspring. Given the rise in the prevalence of metabolic syndrome (MetS), a clinical condition closely related to obesity, it is important to understand the molecular mechanisms by which maternal MetS might impact offspring behavior and brain function. Ten, two-months-old female Wistar rats from our colony were sep- arated in two groups of five rats each, control (C) and fructose 20% (F). The former drank tap water while the later drank fructose 20 % (w/v) ad libitum during 10 weeks. Both F- and C dams were mated to chow-fed male rats on the 7th week of treatment and maintained on their respective diets throughout pregnancy and sacrificed on day 4 postpartum. At postnatal day (PN) 1, the progeny from both groups were separated from their mothers and continued lactating from control nurse dams. From PN3-PN21 neurodevelopmental re- flexes were evaluated. At PN22 all pups were weaned and behav- ioral tests (open field, marble test, elevated plus maze, novel object recognition, social reciprocal interaction test, tail flick test, rotarod, Kondziela’s inverted screen test) were performed on 4- to 12-week- old female and male rats. Results were considered statistically dif- ferent between the C and the F group when a p value of 5% or lower (p< 0.05) was obtained when applying the t-student test. Our findings strongly associate maternal fructose consumption with the induction of MetS and infertility. In addition, offspring from the F group presented alterations in the developmental milestones and social behavior; decreased grip strength and increased anxiety. Fur- thermore, long term memory also showed a tendency to be reduced. No modifications were noted in compulsive like behaviors, locomo- tion nor in nociception. All in all, maternal fructose consumption im- pacts on the developmental outcome of its progeny.